Community Participation of the Flood Risk Management in Champhone District, Savannakhet Province - SIBOUNHEUANG, Bangon; keokhamphui, Keoduangchai; Chanthavongsa, Khamkeng (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This article is a study of community participation in flood risk management in 5 villages of Champhone District, Savannakhet Province. The objective of this study is to investigate community participation in flood prevention, flood control, and post-flood recovery among residents affected by the floods that occurred in 2019, 2020, and 2024. The scope of this study is focused on community participation in flood prevention, control, and recovery. The research instrument used in this study was an interview, in which the researcher interviewed a total of 307 affected households, meaning that the sample group for this study was households affected by the floods. The study used an average participation criterion. The results of the study found that communities were involved in flood prevention, control and recovery to a high degree in a number of activities such as flood risk mapping, evacuation planning, flood warnings monitoring , having telephone numbers of key stakeholders, moving essential items and livestock, flood prevention dike construction, helping to clean up homes, planting food crops immediately, and providing damage information to relevant organizations. Most other activities are classified as moderate participation. A small sample group lacked preparedness to respond to floods and complete rehabilitation of their homes due to budget constraints.